La metafísica como la ciencia de la esencia: E. J. Lowe y Tomás de Aquino. (2013)
Metaphysics after being ignored for years has returned to the center of the stage in contemporary philosophy. Thomas Aquinas has lived a very similar story; which gave birth to analytical Thomism. Despite the work done in this line of research; the metaphysics of Aquinas has been heavily ignored. However; the metaphysics of Thomas Aquinas has an advantage; little discussed among Thomists and Tomasinos ; and it is the fact that it is essentialist metaphysics. So; in keeping with the work of metaphysical E. J. Lowe; who presents his metaphysics as serious essentialist it is shown here that the metaphysics of Aquinas has the same virtues of serious essentialism ; which allows to postulate it as a valid and plausible position for contemporary metaphysics.